2011
DOI: 10.1039/c0sm01354d
|View full text |Cite
|
Sign up to set email alerts
|

Semi-permeable vesicles composed of natural clay

Abstract: We report a simple route to form robust, inorganic, semi-permeable compartments composed of montmorillonite, a natural plate-like clay mineral that occurs widely in the environment. Mechanical forces due to shear in a narrow gap assemble clay nanoplates from an aqueous suspension onto air bubbles. Translucent vesicles suspended in a single-phase liquid are produced when the clay-covered air bubbles are exposed to a variety of water-miscible organic liquids. These vesicles of clay are mechanically robust and ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 53 publications
3
37
0
Order By: Relevance
“…Subramaniam et al [107] reported a simple method to construct a robust, semi-permeable protocell model by using the clay montmorillonite, which is a soft phyllosilicate type mineral that is abundant on the Earth. Montmorillonite is believed to be possibly involved in the process of the origin of life.…”
Section: Typical Artificial Cellsmentioning
confidence: 99%
“…Subramaniam et al [107] reported a simple method to construct a robust, semi-permeable protocell model by using the clay montmorillonite, which is a soft phyllosilicate type mineral that is abundant on the Earth. Montmorillonite is believed to be possibly involved in the process of the origin of life.…”
Section: Typical Artificial Cellsmentioning
confidence: 99%
“…It is conceivable that the small spaces behave like cells. Further, when clay minerals are dispersed in water, bubbles form in water or the surface of water, while the clay particles gather at the boundary between water and air, as shown in Figure 7 [57]. In such a case, clay minerals make a cell-like spherule.…”
Section: Cell Originmentioning
confidence: 99%
“…Significantly, the as‐prepared silica‐stabilized emulsion droplets can be exploited as membrane‐bounded microcompartments for enhanced enzyme‐mediated transformations, or cross‐linked and transferred into a continuous water phase for use as colloidosome‐based protocell models for integrating various biomimetic or biological processes, including cytoskeletal‐like hydrogel assembly, capsule growth and division, synthesis of RNA and proteins via cell‐free gene expression pathways, and membrane gating of encapsulated enzyme reactions . Water‐in‐water clay colloidosomes have also been prepared using unmodified montmorillonite particles by applying wetting procedures to clay‐coated air bubbles suspended in water …”
Section: Introductionmentioning
confidence: 99%